Definitive intensity‐modulated radiotherapy concurrent with systemic therapy for oropharyngeal squamous cell carcinoma: Outcomes from an integrated regional Australian cancer centre. Issue 3 (20th January 2016) - Masoud Rahbari, Reza; Winkley, Lauren; Hill, Jacques; Tahir, Abdul Rahim Mohammed; McKay, Michael; Last, Andrew; Shakespeare, Thomas P; Dwyer, Patrick
Abstract: Introduction: Oropharyngeal squamous cell carcinoma (OPSCC) incidence has increased over the past two decades largely because of an increase in human papilloma virus (HPV)‐related OPSCC. We report here outcomes of definitive radiation therapy for OPSCC with simultaneous integrated boost intensity‐modulated radiotherapy (IMRT) in a regional Australian cancer centre. Methods: We retrospectively reviewed electronic medical records (EMR) of all patients treated with IMRT for head and neck cancer. We included patients who received a curative intent IMRT for OPSCC (2010–2014). Results: Of 61 patients, 80% were men, and the median age was 57 years. Ninety percent of our patients received concurrent systemic therapy, and 68% were p16 positive. The median radiotherapy dose received was 70 Gy in 35 fractions. The median follow up for surviving patients was 22 months. Twenty‐four month actuarial data show that the loco‐regional recurrence free, metastasis‐free MFS, cancer‐specific (CaSS) and overall survival percentages were 98.3%, 92.6%, 91% and 90.3%, respectively. We did not observe grades 4 or 5 acute or late toxicities, and 10 patients (16.2%) exhibited persistent grade 3 toxicity 6 months after completing the treatment. Conclusion: The results from curative IMRTs for OPSCC delivered in a regional cancer centre are comparable with results published by tertiary referral centres. A long‐term follow up of this patient cohort will continue for further analyses and comparisons with tertiary centres.